2001
DOI: 10.1116/1.1417545
|View full text |Cite
|
Sign up to set email alerts
|

Observation and characteristics of mechanical vibration in three-dimensional nanostructures and pillars grown by focused ion beam chemical vapor deposition

Abstract: Articles you may be interested inNonlinear large deflection of nanopillars fabricated by focused ion-beam induced chemical vapor deposition using double-cantilever testing Mechanical characteristics and applications of diamondlike-carbon cantilevers fabricated by focused-ion-beam chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 6 publications
3
85
0
Order By: Relevance
“…We have previously reported that amorphous carbon pillars grown by focused ion beam induced chemical vapor deposition (FIB-CVD) technique [17,18], containing a certain amount of Ga that comes from as the ion species, were turned into multi-walled graphite tubes when a biasing voltage was instantly applied [19]. Here, the distinctive feature of the transformed pillar was gallium droplets coexistence with the graphite partition inside the graphitized tube, and the outside of the tube still remained as an amorphous carbon.…”
mentioning
confidence: 99%
“…We have previously reported that amorphous carbon pillars grown by focused ion beam induced chemical vapor deposition (FIB-CVD) technique [17,18], containing a certain amount of Ga that comes from as the ion species, were turned into multi-walled graphite tubes when a biasing voltage was instantly applied [19]. Here, the distinctive feature of the transformed pillar was gallium droplets coexistence with the graphite partition inside the graphitized tube, and the outside of the tube still remained as an amorphous carbon.…”
mentioning
confidence: 99%
“…A slight shift in beam position causes shifts in secondary electrons and its distribution, so the growth moves from its place and starts from the side of the fabricated structure. The combination of this lateral growth mode with shifting beam scanning provides the growth of 3-D structures [ 45 ]. At the same time with the continuous rotation in the lateral growth it is possible to achieve a rotational symmetry like a wineglass or a boll.…”
Section: Fabrication Of 3-d and Complex Micro-and Nanostructuresmentioning
confidence: 99%
“…The key issue in making such 3D work is the shallow penetration depth of ions (a few tens of nanometers), which reduces the dispersion area of secondary electrons, and thus the deposition area is tightly limited to within about several tens of nanometers. We also reported that diamond-like-carbon (DLC) pillars grown by FIB-CVD with a precursor of phenanthrene vapor have a very large Young's modulus that exceeds 600 GPa, which provides outstanding characteristics for various applications [2]. electron-beam chemicalvapor-deposition (EB-CVD) is also well known for its ability to produce nanostructures, which has been demonstrated to fabricate 3D nanostructures with feature sizes down to a few tens of nanometers [3].…”
Section: Introductionmentioning
confidence: 97%